RESPON PERTUMBUHAN DAN PRODUKSI BENGKUANG (Pachyrhizus erosus (L.) URBAN) TERHADAP WAKTU PEMANGKASAN DAN JARAK TANAM - Ferdinandus DM. Panggabean; Lisa Mawarni; T. Chairun Nisa (Jurnal Agroekoteknologi, 2014)
The objective of this research was to determine the right pruning times and spacing for the growth andproduction of yam (Pachyrhizus erosus (L.) Urban). This research used factorial randomized blockdesigned with 2 factors and 3 replications. The first factor was pruning time (P),namely withoutpruning (PA), pruning 7 weeks after planting (PB) and pruning 8 weeks after planting (PC) Thesecond factor was spacing (J) which consisted of 20 x 10 cm (J1), 20 x 15 cm (J2),20 x 20 cm (J3),and 20 x 25 cm (J4). The results showed that pruning significantly increased length of plant andnumber of branches. The treatment of spacing area influenced plant height. Interaction of pruningtimes and spacing increased plant height and number of branches.Key words : Yam, Pruning times, Spacing plants.